2017
DOI: 10.1111/jfbc.12398
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of silymarin and naringin on methotrexate-induced nephrotoxicity in rats: Biochemical evaluation of anti-inflammatory, antiapoptotic, and antiautophagic properties

Abstract: Silymarin (SLY) and naringin (NRG) are natural flavonoids that have been reported to have many benefits and medicinal properties. The present study was designed to investigate the protective effect of SLY and NRG against methotrexate (MTX)‐induced nephrotoxicity in experimental animals. Rats were subjected to oral pretreatment of SLY (25 and 50 mg/kg body weight (b.w.)/day) and NRG (50 and 100 mg/kg b.w./day) for 7 days against renal toxicity induced by single intraperitoneal administration of MTX (20 mg/kg b.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
59
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 113 publications
(70 citation statements)
references
References 53 publications
9
59
0
2
Order By: Relevance
“…Methotrexate (MTX) is an antineoplastic drug widely applied in the treatment of cancers and non‐cancerous diseases like rheumatoid arthritis and psoariasis (Kandemir et al, ). MTX inhibits enzymatic incorporation of reduced folate into nucleotide synthesis, thus inhibiting DNA synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methotrexate (MTX) is an antineoplastic drug widely applied in the treatment of cancers and non‐cancerous diseases like rheumatoid arthritis and psoariasis (Kandemir et al, ). MTX inhibits enzymatic incorporation of reduced folate into nucleotide synthesis, thus inhibiting DNA synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that MTX enhances free radical production in brain tissue to decrease antioxidant defense system leading to oxidative stress and MTX‐induced neurotoxicity (Uzar et al, ). However, recent investigations have associated MTX‐induced oxidative stress to inflammatory cascades via increased levels of cytokines and nuclear factor‐ĸB expression in renal tissue (Kandemir et al, ; Rashid et al, ). Brain is vulnerable to oxidative injury because of its low antioxidant defenses, high‐energy demand and saturated fatty acids (Soni, Prakash, Dabur, & Kumar, ).…”
Section: Introductionmentioning
confidence: 99%
“…Lipid peroxidations are responsible for the various diseases, such as atherosclerosis, aging, radiation injury, cancer, and inflammation (Alim & Beydemir, ). Several in vitro studies have reported that polyphenols have important radical scavenging features (Caglayan, Temel, Kandemir, Yildirim, & Kucukler, ; Kandemir, Kucukler, Caglayan, et al, ). Also, a number of studies have determined that polyphenols play role inhibit LDL oxidation, which is a significant factor in the onset of coronary heart disease and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Orange juice includes flavonoids related to antioxidant activity. Naringin (Kandemir, Kucukler, Caglayan, et al, ) and hesperidin (Ekinci Akdemir et al, ) are glycosides and primarily report to the protective and antioxidant activities. They found in orange peel and play a key role against damaging biological oxidative stress (Kanaze et al, ) PON1, an anti‐inflammatory and antioxidant enzyme found in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is a cellular response frequently induced by oxidative stress stimulation (Gill et al, 2010; Kandemir et al, 2017a,b). It is critically involved in both normal brain development and injury during embryogenesis.…”
Section: Discussionmentioning
confidence: 99%